Solace in sound: Glenn Gould's electronic solitude. Issue 1 (1st March 2021) - Hicks, Steven
Inspired by Marshall McLuhan, pianist Glenn Gould dedicated his career to polemics against the concert hall tradition. Through radio/television broadcasts, written works and contentious recorded catalogue, Gould advocated adoption of the new electric media environment of the mid-twentieth century, challenging musical traditions of centuries past. Gould also used telephonic technology to mediate contact with the outside world. Gould has been acknowledged by such authors as Paul Théberge as putting into practice the ideas of Marshall McLuhan. In this study, I follow Robert Logan's work in media ecology and general systems and investigate Gould's polemics through systems theory. In particular, I employ Niklas Luhmann's theory of social systems, offering a model of society through which we may observe the effects of electric technology via the notion of functional de-differentiation of social systems as discussed by authors such as Erkki Sevänen. I suggest that Gould's polemics are not just commentary on musical tradition but the media environments in which those traditions arose and show how we too can find solace in sound.